Eksplorasi Dimensi-Dimensi Lived Religion Dalam Nyanyian Osong Rambu solo’ di Kabupaten Luwu - Ghiland, Ghiland; Lattu, Izak Yohan Matriks; Tampake, Tony Robert Christian (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Religious practices in society are often understood in a limited sense within formal spaces, doctrines, or specific institutions, which can lead to stigmatization and intervention in local cultural expressions and beliefs. This study aims to demonstrate that Osong functions not only as part of a cultural tradition but also embodies religious practices that transcend the boundaries of formal and institutionalized religion. This research employs ethnographic methods to gain an in-depth understanding of social and religious practices in daily life, particularly in the context of Osong. The findings reveal that the Osong song in the Rambu solo’ ritual contains various dimensions of lived religion, such as spirituality, embodiment, materiality, aesthetics, emotion, morality, and narrative. Each of these dimensions not only highlights the community’s relationship with the transcendent but also strengthens social solidarity and the cultural identity of the Toraja people in facing the realities of death and social changes in their environment. These findings affirm that religious practices lived by the community are not always dependent on formal institutions but can manifest in local cultural spaces that are alive and evolving within the community.